Introduction to the English Legal System - Partington, Martin (Oxford University Press, 2021)
Introduction to the English Legal System is the ideal foundation for those new to the study of law. Writing in a highly engaging and accessible style, Partington introduces the purposes and functions of English law, the law-making process, and the machinery of justice, whilst also challenging assumptions and exploring current debates